An unusual intracardiac image. (16th November 2012) - Lahlou, Zineb; Salimi, Soundousse; Dehbi, Fatima
Abstract : One of the most serious complications in cardiovascular surgery is the unintentional deposit of material and surgical instruments. Very few articles portray these complications in children. This is not the case with regard to interventional and surgical cardiovascular procedures in adults. We report a case concerning a cystic heart image related to a cardiac iatrogenic foreign body in a girl of 14 years. She has been operated 13 years ago for patent ductus arteriosus and aortic stenosis and currently she is admitted for a cyanosis and a dyspnoea.